Syntactic and semantic features of the sensory verbs group in English and their Vietnamese equivalents / Ngo Thi Lan Anh; NHDKH Assoc.Prof.Dr Phan Van Que - Ngo, Thi Lan Anh
The verb is perhaps the most important part of the sentence. A verb states what is happening in the sentence. Among verbs of English, we find that the sensory verbs see, hear, feel, smell, taste are quite frequently used. Special attention is paid to different senses governed by contexts where these five verbs are used. In order to help Vietnamese learners of English to have a deep understanding of other nuances of meanings conveyed by these English verbs, their Vietnamese equivalents are examined. The participants of the study are five English verbs see, hear, feel, smell, taste which are taken from different sources such as dictionaries, books, novels in English and Vietnamese. The data are collected by the activities of reading the materials, identifying and classifying. The data in this study are analyzed by explaining them in terms of their meanings and syntactic features. The results of the study show that the five English verbs of the sensory verb group in English under discussion can occur in the same syntactic patterns, but may have different meanings depending on the situation in which they are used and they can occur in different syntactic patterns that reflect various meanings in real-life communication. A further pedagogical implication resulting from the findings included in this study could be equally beneficial for teachers and learners who would like to expand their knowledge concerning the most typical ways of perspectivising the linguistic scene by means of the sensory verb group in English